REGULASI WAKAF DI INDONESIA PASCA KEMERDEKAAN DITINJAU DARI STATUTE APPROACH - Sudirman, Sudirman (De Jure: Jurnal Hukum dan Syari'ah, 2014)
This Article focusing on wakaf regulation in Indonesia after its independence day. The research used statute approach, it also used regulation No. 5 Year 1960 and regulation No. 41 Year 2004 as its primary legal source. In analyzing data it used three legal basis; Lex Superior Derogat Legi Inferiori, Lex Specialis Derogat Legi Generali, and Lex Posterior Derogat Legi Priori.Â  Firstly, it concludes that the background of regulating the wakaf regulation in Indonesia was conducted because of public needs to a special regulation which can rules wakaf and its legal contemporary development. Secondly, the comparison of wakaf regulations regulated from post-independence until reformation era explained that in the first concept of wakaf and its implementation opportunity was realized in The Reg. 5/1960. But the concept of NÃ¢dzir firstly introduced in Gov. Regulation No. 28/1977 and established by the Indonesian compilation of Islamic Law. Thirdly, penal punishment changes, and according to statute approach analysis using those three legal basis, the Reg. 41/2004 is the most updated wakaf regulation in Indonesia.